he correlation between fear of infection with coronavirus disease 2019 and the mental health of pregnant women - Sepideh Dinmohammadi; Giti Ozgoli; Shabnam Towfighi; Malihe Nasiri; Fatemeh Bayat (Zanjan University of Medical Sciences and Health Services, 2024)
Background: Pregnancy is a physiological phenomenon accompanied by numerous physical and psychological changes. Fear of contracting diseases such as coronavirus disease 2019 (COVID-19) or other illnesses for which scientific knowledge is still incomplete can create anxieties in pregnant women, impacting their mental health. Objectives: The present study aimed to determine the association between fear of infection with COVID-19 and the mental health of pregnant women. Methods: A cross-sectional study was conducted on 164 pregnant women attending Ayatollah Mousavi Hospital in Zanjan, Iran, in 2021. Participants were randomly selected. Data were collected using demographic questionnaires, the Depression, Anxiety, and Stress Scale (DASS-21), and the Fear of Disease Coronaviruses Scale (FDCS). Data were analyzed using Spearman's correlation coefficient and simple linear regression in SPSS 21 software. Results: Results demonstrated that 23.4% of participants experienced anxiety, 18.2% experienced depression, and only 1.2% experienced stress. Fear of infection was positively and significantly correlated with anxiety (r= 0.18, p=0.01). Additionally, income adequacy (r= -0.24, p=0.002), perceived economic status (r= -0.16, p=0.04), and spousal support (r= -0.19, p=0.01) were also negatively and significantly correlated with fear of infection. Conclusion: Findings reveal that the COVID-19 pandemic can culminate in fear and anxiety in pregnant women. Spousal support during this sensitive period and feelings of marital satisfaction can relieve anxiety in women.